Pendampingan dan Pelatihan Pembuatan Pembukuan Sederhana bagi Pelaku UMKM di Desa Argomulyo, Kecamatan Sedayu, Kabupaten Bantul, Daerah Yogyakarta - Nor Laili Fitri Ameliah; Nugraeni Nugraeni (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Bookkeeping is an important part of running a business. This simple bookkeeping assistance and training activity was carried out in Argomulyo Village, Sedayu District, Bantul Regency, Yogyakarta Region by taking 2 samples of MSME actors, namely “Grocery Store” owned by Mrs. Ina and “angkringan soto” owned by Mrs. Yuningsih. Based on the results of interviews and observations that have been made, there are several problems of these MSME business actors, which are almost the same, including that MSME actors have not made financial records consistently and there is no separation of records between business capital and personal finances. Therefore, from these problems, assistance and training in making simple bookkeeping have been carried out using materials consisting of modules related to MSME financial accounting. Assistance and training in bookkeeping for MSME actors in Argomulyo Village aims to improve the ability of MSME actors to manage their business finances. The method used for this community service activity is to provide training in bookkeeping and mentoring the material provided consists of modules that are guided by MSME financial accounting. The result of this activity is that with the training and mentoring activities related to simple bookkeeping, MSME actors already know the importance of implementing simple bookkeeping in their business and can distinguish between business capital and personal finances